Seasonal Carbohydrate Changes in the Leaves of Some Satsuma Cultivars on Different Rootstocks - Turan Hakan Demirkeser; Mustafa Kaplankıran; Celil Toplu; Ercan Yıldız (Journal of Agricultural Sciences)
The seasonal changes of carbohydrate content were monitored in the leaves of ‘Okitsu’, ‘Clausellina’, and ‘Silverhill’satsuma cultivars budded on the sour orange (Citrus aurantium L. var. Yerli), Carrizo and Troyer citranges (Poncirustrifoliata Raf. x Citrus sinensis Osb. var. Troyer and Carrizo) during the 2010 and 2011 seasons. The seasonal changingtrends of leaf soluble sugar contents of 3 satsuma cultivars budded on different rootstocks were similar. The sucrose wasthe most abundant soluble sugar. Carbohydrate contents had a maximum level at dormant period, and remained at lowlevel during summer. In this period, the sharp decrease in leaf total carbohydrate concentration of ‘Okitsu’, ‘Clausellina’and ‘Silverhill’ occurred in April with a rate of 27.9%, 22.6% and 21.0%, respectively. Accumulation of carbohydratein leaves generally started after mid summer and continued until the end of year. The rootstocks were found to be notsignificant for total soluble sugar, starch and total carbohydrate concentration in most of the months. The cultivars hada significant effect on carbohydrate fractions of leaves compared to rootstocks. The scion-rootstock combination wassignificant on total carbohydrate concentration of leaves in all months investigated.